HUBUNGAN MULTIPLE INTELLIGENCES DENGAN HASIL BELAJAR BIOLOGI SISWA KELAS X SMAN DI KOTA PADANG - Selaras, Ganda Hijrah; Anhar, Azwir; Sumarmin, Ramadhan (Kolaboratif, 2013)
Based on the fact that many teachers still did not knew the multiple intelligences level of students. Whereas the teachers can be helped to decide the appropriate learning strategy and to form learning groups with knowing multiple intelligences level of students. This research head for knowing the relationship of multiple intelligences of students with the biology learning result of Senior High School students. This research is a descriptive research with correlation approach. The population of this research are grade X students of Senior High Schools in Padang. This research used proportionate stratified random sampling. The technique and instrument of data collection are questionnaires in order to know students multiple intelligences level and documentations for acquiring Senior High School students biology learning result. Hypothesis is tested by using Spearman-Rank correlation test. The result of this research showed that two intelligences have low correlation, those are linguistics intelligence and logical mathematical intelligence with correlation coefficient as big as 0,33 and 0,35. Six intelligences else have criteria with very low. As a whole multiple intelligences have low relation with biology learning result of Senior High School students. The correlation coefficient is as big as 0,30. So the biology learning result of Senior High School students tended to increase along with the increasing of multiple intelligences level. We can conclude that multiple intelligences level and biology learning result of Senior High School students in Padang have significantly positive relationship.